ISLAMIZATION IN SINJAI IN THE 17TH CENTURY: THE ARRIVAL OF ISLAM AND SOCIAL CHANGE - Hasaruddin, Hasaruddin; Mania, Sitti; Anis, Muh. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
This study aims at describing the arrival of Islam in the form of Islamization that resulted in socio-political and cultural change in Sinjai Society. It is examines the role of the authorities who collaborate with Islamic scholars in the process of Islamization in Sinjai. This study involved qualitative research, and the data comprised both oral and written sources. The oral sources were conducted through interviews with several people who were considered to have required competence and trustworthiness. Written sources were derived from Lontara manuscripts, books and reports of the results of previous studies, articles, and internet websites. The research found that the arrival of Islam in Sinjai originated in three regions. The first was the East region in Tiro in which Abdul Jawad Khatib Bungsu or Datuk ri Tiro stayed in his mission to spread Islam in the southern area of South Sulawesi. The second was the West region in Gowa in which Abdul Makmur Khatib Tunggal or Datuk ri Bandang stayed to teach and spread Islam. The third was North region in which Laming or Wali Pute, the person who delivered Islamic teachings from Pompanua-Bone, came to spread Islam, especially in the Kingdom of Lamatti. There was the process in arrival of Islam in Sinjai society, however, it was not necessarily directly accepted, especially by the authorities. The authorities conducted process of the arrival of Islam through public figures from 1604 to 1607. The arrival and the spread of Islam led to sara’ (Islamic law) as an integral part of pangngadereng (customary law). Therefore, the regulations of South Sulawesi society in Sinjai acquired a new framework, where sara’ influenced behavior and social life. The adherence of society to sara’ was due to the presence of Islam, which affected values, social norms, and culture from what previously existed. Islam altered the cultural aspects of society, since upon the arrival of Islam, the Ulama (the Islamic scholars) focused on faith and the truth of monotheism.